2020
DOI: 10.1073/pnas.1912910117
|View full text |Cite
|
Sign up to set email alerts
|

Oncostatin M-induced astrocytic tissue inhibitor of metalloproteinases-1 drives remyelination

Abstract: The brain’s endogenous capacity to restore damaged myelin deteriorates during the course of demyelinating disorders. Currently, no treatment options are available to establish remyelination. Chronic demyelination leads to damaged axons and irreversible destruction of the central nervous system (CNS). We identified two promising therapeutic candidates which enhance remyelination: oncostatin M (OSM), a member of the interleukin-6 family, and downstream mediator tissue inhibitor of metalloproteinases-1 (TIMP-1). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
1
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 62 publications
1
29
1
1
Order By: Relevance
“…Additionally, also astrocytes may influence the outcome of remyelination. They can be beneficial for remyelination by promotion of oligodendroglial differentiation and providing of cholesterol for new myelin sheaths, but have been also shown to impair remyelination by either activating remyelination inhibiting pathways such as the JAG1-NOTCH1 pathway or by modulating the extracellular matrix [10,32,35,61,72]. One also has to keep in mind that the biopsies were taken from patients with an untypical clinical presentation and, therefore, might not be representative for MS patients with a more typical disease onset.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, also astrocytes may influence the outcome of remyelination. They can be beneficial for remyelination by promotion of oligodendroglial differentiation and providing of cholesterol for new myelin sheaths, but have been also shown to impair remyelination by either activating remyelination inhibiting pathways such as the JAG1-NOTCH1 pathway or by modulating the extracellular matrix [10,32,35,61,72]. One also has to keep in mind that the biopsies were taken from patients with an untypical clinical presentation and, therefore, might not be representative for MS patients with a more typical disease onset.…”
Section: Discussionmentioning
confidence: 99%
“…In the context of a traumatic lesion of the CNS, MMPs including Timp1 are critical for synaptic recovery following axonal injury, mediating secondary degeneration and regulating angiogenesis and glial scar formation [ 47 ]. Timp1 also has pro-oligodendroglial properties in different in vitro contexts which promote OPC maturation [ 48 ] and in vivo inhibition of Timp1 activity completely abolishes spontaneous remyelination [ 49 ]. This protein is also associated with various integrins, including ItgaV, Itgb1 and Itgb3, which are involved in OPC differentiation into myelinating oligodendrocytes [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…We found that Dectin-1 promotes expression of Osm, a cytokine with described protective functions in cuprizone-induced demyelination 17,77 and other models of neuropathology 16,37 . Osm protein is expressed in MS brains 38 and is elevated in supernatants of cultured PBMCs from MS patients 39 .…”
Section: Studies On Clrs In Eae and Related Models Have Mostly Focusementioning
confidence: 79%